Las denominadas expresiones diferenciales en español - Devís Márquez, Pedro Pablo (El Colegio de México, 2013)
This work focuses on non-comparative quantifiers occuring withinSpanish comparative constructions of inequality. These non-comparativequantifiers are often referred to as differential ({pocos/bastantes/muchos/dos veces…} {más/menos} {bueno/lejos}). Specifically, the articledeals with the extensional boundaries of this class of units, their cooccurrencecontexts, their syntactic and semantic relationships withinthe comparative phrase, their behavior in inequality comparative constructionsbased on discrete quantities, their semantic compatibilitywith the comparative head (and the influence of metaphorical processes therein), and their occurrence in non-comparative environments.